Cardiac remodelling in experimental renal failure: an immunohistochemical study - Amann, Kerstin; Kronenberg, Golo D.; Gehlen, Frank; Wessels, Sabine; Orth, Stefan; Münter, Klaus; Ehmke, Heimo; Mall, Gerhard; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1998)
BACKGROUND: In view of the high rate of cardiac death in renal failure, the factors involved in the genesis of structural changes in the heart are of obvious interest. The present study addresses the issue whether growth factors known to be involved in cardiac remodelling are abnormally expressed in rats with renal failure. METHODS: Sprague Dawley rats were subjected to binephrectomy (2 days) or subtotal nephrectomy (8 weeks). Controls were sham-operated rats and rats with Goldblatt hypertension. Cardiac expression of proliferating cellular nuclear antigen (PCNA), of growth factors and of their receptors (PDGF, TGF-beta, VEGF) was investigated immunohistochemically. In addition, cardiac PDGF-and TGF-beta mRNA were assessed using quantitative RT-PCR. RESULTS: Eight weeks after subtotal nephrectomy (SNX) significantly increased expression of PCNA and PDGF was found in the cardiac interstitium and of PCNA and VEGF in the walls of intramyocardial arteries. In addition, PCNA-positive cardiomyocytes were noted in SNX. Similar changes were not seen in the hearts of hypertensive controls, i.e. rats with renovascular hypertension, despite slightly higher blood pressure and more pronounced left ventricular hypertrophy (LVH). While significant changes of cardiac PDGF- and TGF-beta mRNA expression could not be documented in the whole-heart homogenates 8 weeks after subtotal nephrectomy, 2 days after bilateral nephrectomy PDGF mRNA was significantly increased and TGF-beta mRNA decreased. CONCLUSION: The observations demonstrate (i) specific activation of cardiac interstitial cells after SNX, (ii) activation of postmitotic cardiomyocytes, possibly predisposing to apoptosis, (iii) increased expression of PDGF in the cardiac interstitium and in the wall of intramyocardial arteries, (iv) increased expression of VEGF associated with hypertrophy of arterial smooth muscle cells. These results were not explained by elevated blood pressure or LVH, respectively.